Decrease in eccentric hamstring strength in runners in the Tirol Speed Marathon - Koller, A.; Sumann, G.; Schobersberger, W.; Hoertnagl, H.; Haid, C. (British Journal of Sports Medicine, 2006)
Background: The local muscular endurance of knee flexors, during eccentric work in particular, is important in preventing or delaying kinematic changes associated with fatigue during treadmill running. This result, however, may not be transferable to overground running.